2019
DOI: 10.1371/journal.pone.0218742
|View full text |Cite
|
Sign up to set email alerts
|

Complexation and conformation of lead ion with poly-γ-glutamic acid in soluble state

Abstract: Complexation of microbial polymer in soluble state could impact the solubility, mobility, and bioavailability of heavy metals in the environment. The complexation of a bacterial exopolymer, poly-γ-glutamic acid (γ-PGA), with Pb2+ was studied using the polarographic method and circular dichroism measurement in soluble state. The number of available binding sites was determined based on the Chau’s method and was found to be 0.04, 1.12, 3.56 and 4.51 mmol/(g dry weight of γ-PGA) at pH 3.4, 4.2, 5.0 and 6.2, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…Specifically, at a γ-PGA concentration of 0.5%, the adsorption rates for Pb ions were observed to be 1.07 and 1.19 times greater than those for Cu and Cd ions, respectively. This pattern of adsorption behavior is consistent with previous research, which suggests that the biosorption capacity of γ-PGA is significantly influenced by its coordination mode and conformation changes upon metal ion complexation [ 48 ]. A critical aspect of this observation is the role of structural modifications in γ-PGA that occur upon complexation with Pb 2+ ions.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Specifically, at a γ-PGA concentration of 0.5%, the adsorption rates for Pb ions were observed to be 1.07 and 1.19 times greater than those for Cu and Cd ions, respectively. This pattern of adsorption behavior is consistent with previous research, which suggests that the biosorption capacity of γ-PGA is significantly influenced by its coordination mode and conformation changes upon metal ion complexation [ 48 ]. A critical aspect of this observation is the role of structural modifications in γ-PGA that occur upon complexation with Pb 2+ ions.…”
Section: Resultssupporting
confidence: 92%
“…As previously discussed, these mechanisms include ion exchange processes and chemical interactions that are influenced by the specific properties of the metal ions, such as their electronegativities and tendencies to form complexes. The preferential adsorption of Pb ions over Cd ions may be due to a more favorable interaction between Pb ions and the functional groups present in Na-γ-PGA-HM [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tis could be attributed due to the saturation of binding sites, altered protein conformation, competitive binding with other ions, pH and ionic changes, solubility limits, and potential protein aggregation. Additionally, elevated zinc sulfate concentrations could facilitate protein-protein interactions, impacting site accessibility and binding efciency [43]. Our study aligns with Shilpashree et al [44], who found maximum zincbinding capacity at 2 mM Zn concentration.…”
Section: Zinc-binding Efciency Of Ppcsupporting
confidence: 90%
“…Xiao et al (2019) reported the removal of copper (II) oxide and hexavalent chromium from wastewater using biochar in a mechanism which includes complexation. The organisms that have been reported to be involved in complexation include Rhodobacter blasticus (Bai et al, 2019) and B.lichenformisis (Wang et al, 2019).…”
Section: Biosorptionmentioning
confidence: 99%